Disease activity and functional outcomes in non-radiographic spondyloarthritis versus ankylosing spondylitis – preliminary results - Ana-Maria Doca; Andreea Odobasu; Andreea Hortolomei; Mara Russu; Alexandra Popescu; Cristina Pomirleanu; Georgiana Strugariu; Codrina Ancuta (Romanian Journal of Rheumatology, 2022)
Introduction. Spondyloarthritis (SpA) represent a heterogeneous group of chronic inflammatory conditions sharing clinical, genetic, imaging and therapeutic features. Objectives. To analyze the clinical and biological characteristics, disease activity and functional impact in non-radiographic axial SpA (nr-axSpA) versus ankylosing spondylitis (AS). Material and method. Cross-sectional observational 12 months study on 46 patients with axial SpA; disease related parameters (clinical, biological, activity and functionality indices) and treatment options were compared in disease categories (nr-axSpA and AS). Outcomes. AS was diagnosed in 73.9%, and nr-axSpA in 26.1% cases. The majority of patients with nr-axSpA were women (72% vs 28%), with a younger age at onset (35.2±9.5 years vs 41±0.6 years) and a shorter time to diagnosis (3±0.5 vs 5.5±3.2 years). C-reactive protein levels were significantly higher in AS compared to nr-axSpA (2.2±0.5 vs 1.28±0.7) (p<0.05). However, there were no significant differences between activity (ASDAS-CRP: 3.4±1.2 vs 3.2±0.9; BASDAI: 5.8±1.3 vs 5.6±1.1) and functionality measures (BASFI: 5.8±1.4 vs 5.7±1.2) in (p >0.05) in AS vs nr-axSpA. Conclusions. Although nr-axSpA occurs frequently in women and may present with lower CRP levels, there are similar trends in disease activity and functional outcomes in both disease categories of the ax-SpA spectrum. Both nr-axSpA and AS patients experience high disease burden.